Racial Disparity in Federal Criminal Sentences - Rehavi, M. Marit (2014)
Using rich data linking federal cases from arrest through to sentencing, we find that initial case and defendant characteristics, including arrest offense and criminal history, can explain most of the large raw racial disparity in federal sentences, but significant gaps remain. Across the distribution, blacks receive sentences that are almost 10 percent longer than those of comparable whites arrested for the same crimes. Most of this disparity can be explained by prosecutors’ initial charging decisions, particularly the filing of charges carrying mandatory minimum sentences. Ceteris paribus, the odds of black arrestees facing such a charge are 1.75 times higher than those of white arrestee